Teachers' autonomy support and student engagement: A systematic literature review of longitudinal studies - Yang, Dong; Chen, Peng; Wang, Huanhuan; Wang, Kai; Huang, Ronghuai (Frontiers in Psychology, 2022)
Autonomy support is one of the most crucial determinants of teaching practice for student engagement. No literature review on the relations between autonomy support and student engagement existed to the best of our knowledge. Therefore, this study present a systematic literature review from perspectives of landscapes, methodology characters, and autonomy supportive strategies. Overall, 31 articles were reviewed. Followed by PRISMA guidelines, the results yielded several interesting facts: First, studies on such topic surged starting from 2015 and were mostly conducted in United States (32%) and Korea (16%). Publications were scattered, but heavily gathered around psychological and educational journals such as Journal of Educational Psychology (9.7%); Learning and Instruction (9.7%). Most often, studies recruited participants from upper secondary school (58%). Data were collected using solely questionnaire (93.5%) following a two-wave design (51.6%), and were analyzed applying structural equation models (48.4%). Moreover, most of the studies failed to provide concrete autonomy-supportive teaching strategies. Instead, quite often studies (93%) investigated its relations with student engagement from a macro perspective. Within mentioned strategies, they were mostly related to teaching process, there is limited investigation of autonomy supportive teaching practice used before and after instruction. Limitations and suggestions for future studies were provided accordingly.